2021
DOI: 10.1111/1759-7714.14095
|View full text |Cite
|
Sign up to set email alerts
|

Impact of coexistent preserved ratio impaired spirometry on the survival of patients with lung cancer: Analysis of data from the Korean Association for Lung Cancer Registry

Abstract: Background: Preserved ratio impaired spirometry (PRISm) is a common spirometric pattern that is associated with respiratory symptoms and higher mortality rates. However, the relationship between lung cancer and PRISm remains unclear. This study investigated the clinical characteristics of lung cancer patients with PRISm and the potential role of PRISm as a prognostic factor. Methods: We retrospectively reviewed data collected from 2014 to 2015 in the Korean Association for Lung Cancer Registry. We classified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 40 publications
(64 reference statements)
2
9
1
Order By: Relevance
“…Our study’s results indicating a significant impact are the first such finding in a US general population. Nevertheless, these findings align with research from South Korea which found PRISm increased the risk of mortality from lung cancer [ 59 ].…”
Section: Discussionsupporting
confidence: 88%
“…Our study’s results indicating a significant impact are the first such finding in a US general population. Nevertheless, these findings align with research from South Korea which found PRISm increased the risk of mortality from lung cancer [ 59 ].…”
Section: Discussionsupporting
confidence: 88%
“…[33] Non-small cell and small cell lung cancer patients with PRISm had poorer overall survival with a 62% higher risk of mortality, compared to those with AO or normal lung function. [23] In our cohort study, individuals with AO had a 30% higher risk of lung cancer mortality which was relatively low compared to other studies. For instance, in studies conducted on lung cancer patients, AO was associated with poorer overall and progression-free survivals with more than two times higher mortality risks.…”
Section: Discussionmentioning
confidence: 57%
“…Higher proportions of PRISm could be found in hospital-based or cohorts of high-risk groups. It was as high as 21.3% in the Korean lung cancer registry[23], 16.7% in a Japanese study of individuals over 40 years of age[24], and 17-24% in a hospital study from the University of Iowa[11]. Restrictive patterns of lung function impairment can be observed in interstitial lung diseases such as idiopathic pulmonary fibrosis (IPF).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1,172 patients with poor lung function undergoing VATS were initially selected. According to the prior research (18,22,(26)(27)(28)(29)(30) and following the recent GOLD guidelines (31), we define poor lung function as post-bronchodilator FEV1/FVC < 70%.…”
Section: Patients Inclusionmentioning
confidence: 99%